UPAYA MENGURANGI KESULITAN BELAJAR PEMROGRAMAN CNC MILLING DENGAN STRATEGI GENERATIVE LEARNING - Saputro, Herman; Widiastuti, Indah (Jurnal Inovasi Pendidikan, 2011)
This article presents a class action research in the subject of Computer Numerical Controlled (CNC) at the SMK Murni Surakarta. This research aim is improving student ability to create correct CNC program for mill machine. It is found that last class students performed not quite well in this subject. They had difficulty to create CNC mill program logically. Actually, the students possessed appropriate knowledge to imagine the cutting tool movement from subjects related to conventional machine operation However, students were not able to construct that knowledge to develop CNC codes properly. Therefore this research analyzed possibility to implement learning strategy based on constructivism approach that is generative learning strategy. This strategy is directed to ask students to generate their past knowledge with the result that they can understand what their learned on their ways. There were two cycles conducted during the action research, every cycle was consisted of four phases: planning, action, evaluation and reflection phase. At the first phase of 1st cycle, the teacher prepare teaching plan, course material and assessment instrument. Then, the teacher identified initial knowledge and motivation of students to plan the actions by means of question-naire and pre requisite subject score. The first cycle action is focused on tool movement on coordinate form. The evaluation on this cycle showed that students were able to create knowledge from information they have known and they were capable to determine tool direction. Based on this result, in the second cycle the students were asked to create engineering drawing on the millimeter book together with the tool direction. After that, they simulated it by means of Cutviewer mill. There was an increasing in percentage of students do@ the task correctly (74,3%). It shows that generative learning strategy could be an alternative to reduce students' difficulty in CNC programming learning.